Análise hidromorfológica e da qualidade da água dos ribeirões Espera e Araras localizados no município de Três Pontas-MG - Carneiro, Thaís Siqueira (2018)
Maintaining a better quality of life is often frustrated by growth, due to increased consumption of resources and energy to meet demand and expectations of socioeconomic development. In the last few years, the urban spot has expanded across all regions that concentrate important water supplies. The Espera and Araras streams in Três Pontas, MG, are responsible for the county public water supply and, not unlike other regions of the country, these water courses have also been under significant pressure from the real estate expansion and the development of economic activities. And it is in this scenario that the importance of water monitoring as an instrument for environmental control and management of water resources is inserted. Thus, the general objective in this study was to evaluate the quality situation in which the Espera and Araras streams are located, using analysis of the variables present in the raw water samples, in the historical series from 2011 to 2016 and later, generating the Water Quality Index (WQI), and for the application of the Bavarian Method in specific points of both streams, to designate its hydromorphological conditions. Thereby, analyzes of the variables were performed through the tabulation of data provided by the Autonomous Water and Sewage Service (SAAE) of Três Pontas, MG, composed of pH, solids, turbidity, biochemical oxygen demand, dissolved oxygen, nitrogen , phosphorus, total coliforms and thermotolerant, heavy metals, persistent and recalcitrant pollutants in the environment. With this, it is desired to create a database based on the time -space evaluation through the variables that were above the maximum allowed value for water resources classified in Class 2, inferring on the aspects that have degraded the quality of the water in the place and then determining the WQI for both. The determination of the hydromorphological conditions of the Espera and Araras streams occurred through the Bavarian Method (Mappingandassessmentmethods for thestructureofwaters), used to map the structur e of the quality of the watercourses, as an evaluation of their ecological probity, demonstrating if it is able to support the dynamic processes of its bed. The results obtained were satisfactory for the two water bodies. The average WQI of the Espera stream was 84 (good and great quality) and the Araras stream had a good classification (average WQI of 80). As for the determination of the hydromorphological condition by the Bavarian Method, the Espera stream was classified as unchanged until moderately altered, and the Araras stream, from little changed until considerably altered, when passing through the county headquarters. So, the results infer about concrete actions for the improvement of water quality and also for the reconstruction of the degraded area.